The Design And Implementation Of Computer Network Monitoring And Security System Using Linux Ubuntu Server - Anisa Dewi Sahara; Sapri Sapri; Abdussalam Al Akbar (Jurnal Media Computer Science, 2024)
One system that can carry out network monitoring is using ntopng tool or application. Linux Ubuntu Server is an open source operating system, this operating system is very good for use as a server because it does not require high hardware specifications and can also be obtained for free because it is open source. Ntopng in carrying out network monitoring is very well applied at SMK S 1 Pembangunan of Bengkulu City, this is because at SMK S 1 Pembangunan of Bengkulu City, the computer network in the computer and visual laboratory is used by students, both for learning and teaching activities as well as the media used by students to fill their free time. When monitoring the network, Ntopng can do this based on the IP address of the device connected to the network